2022
DOI: 10.18026/cbayarsos.1034365
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human and Social Capital on Employee Performance in Public Sector

Abstract: İçinde bulunduğumuz bilgi çağı ve ekonomisinde beşeri ve sosyal sermaye çalışanların ve örgütlerin performansını belirleyen temel sermaye türlerinden ikisi olarak görülmektedir. Bu bağlamda çalışmanın konusu beşeri ve sosyal sermayenin kamu personelinin performansı üzerindeki etkileridir. Çalışmanın konusunu oluşturan araştırma kesitsel tipte bir saha araştırması olup; bir yerel yönetim kuruluşunda çalışan 377 kamu personeli üzerinde gerçekleştirilmiştir. Araştırmada beşerî ve sosyal sermayenin çalışanların iş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Another notion from (Rakhmalina et al, 2017), also disclose the different and convenient management of human resources will generate good output for the company. Hereafter, another research conducted on 377 government employees also showed a positive significant effect between human capital and employee performance (Erten & Türkmen, 2022).…”
Section: Resultsmentioning
confidence: 83%
“…Another notion from (Rakhmalina et al, 2017), also disclose the different and convenient management of human resources will generate good output for the company. Hereafter, another research conducted on 377 government employees also showed a positive significant effect between human capital and employee performance (Erten & Türkmen, 2022).…”
Section: Resultsmentioning
confidence: 83%
“…(Bernes, 2000). Human capital theory is the basis for the design of the ICM, where human capital is not only represented by the civil servants of public organisations, but also includes what these people bring and how they contribute to the success of the organisation (Erten & Türkmen, 2022). Human capital represents the collective value of the knowledge, skills, abilities, motivation and life experience of the people who work in public organisations.…”
Section: Career Management In Public Administration Perspectivementioning
confidence: 99%